Additive stimulatory effect of extracellular calcium and potassium on non-transferrin ferric iron uptake by HeLa and K562 cells - Musílková, J; Kovár, J (Biochimica et biophysica acta, 2001)
We studied the effects of Ca(2+) and K(+) on non-transferrin iron uptake from ferric citrate complex by HeLa and K562 cells. Uptake experiments in Na-HEPES buffer (137 mM NaCl, 4 mM KCl) showed that extracellular Ca(2+) stimulated the iron uptake. The rate of iron uptake in 4 mM Ca(2+) was about 3-5 times higher than without Ca(2+). The iron uptake in K-HEPES buffer (68 mM NaCl, 75 mM KCl) with a high K(+) level was transiently stimulated during the first 10 min. The rate of iron uptake for 0.4 mM Ca(2+) was approximately 3 times higher in K-HEPES buffer than in Na-HEPES buffer. The calcium channel blockers verapamil (50 microM) and nifedipine (5 microM) had no effect on the uptake either in control Na-HEPES buffer or after K(+) stimulation in K-HEPES buffer. The sodium channel blocker lidocaine (50 microM) also had no effect on the uptake of iron in Na-HEPES buffer as well as after K(+) stimulation. Furthermore, the iron uptake was not significantly affected when Na(+) in the Na-HEPES and K-HEPES buffers was replaced by isotonic saccharose. We conclude that extracellular calcium per se, and not intracellular calcium or Ca(2+) transport, stimulates ferric iron uptake by both HeLa and K562 cells. A high level of extracellular K(+) also stimulates the uptake, probably via cell membrane depolarization. Na(+) is not involved in these stimulations of iron uptake. The transient K(+) effect and continuous Ca(2+) effect seem to be additive.
Keywords: železité sloučeniny; Potassium; pufry; Calcium; Up-Regulation; draslík; Ferric Compounds; Lithium Chloride; vápník; železo; Buffers; Lidocaine; upregulace; blokátory kalciových kanálů; HeLa buňky; Time Factors; Cell Membrane; buňky K562; biologický transport; lidé; Calcium Channel Blockers; Iron; HeLa Cells; Humans; chlorid lithný; buněčná membrána; časové faktory; K562 Cells; calcimycin; Calcimycin; Biological Transport; lidokain